Serba Serbi Hukum Waris - Richard Chandra Adam (Ethics and Law Journal: Business and Notary, 2024)
In the Civil Code (Civil Code), there are three principles that explain who the heirs are entitled to and can receive the division of inheritance according to the inheritance system established in the Civil Code. The items inherited by a testator can be valuable property, tangible objects, intangible objects, or simply a testamentary message transmitted. This division of inheritance led to family quarrels, led to family discord. The government allows lawsuits related to inheritance if there are problems that can lead to family quarrels. In addition to the Civil Code, it regulates three principles that govern heirs: the personal principle, the bilateral principle, and the principle of succession. Besides that, it also regulates the elements of inheritance law, such as heirs, testators, and inheritance property as property given by the heir to the heir. The civil code also divides heirs into four groups: Group I, Group II, Group III, and Group IV.   Abstrak Dalam Kitab Undang-Undang Hukum Perdata (KUHPerdata), ada tiga asas yang menjelaskan siapa ahli waris yang berhak dan dapat menerima pembagian harta waris menurut sistem pewarisan yang ditetapkan dalam KUHPerdata. Barang-barang yang diwariskan oleh seorang pewaris dapat berupa harta berharga, benda berwujud, benda tidak berwujud, atau hanya pesan wasiat yang dikirimkan. Pembagian warisan ini menyebabkan pertengkaran keluarga, menyebabkan perselisihan keluarga. Pemerintah mengizinkan tuntutan hukum terkait pewarisan jika ada masalah yang dapat menyebabkan pertengkaran keluarga. Selain KUHPerdata mengatur tentang tiga asas yang mengatur ahli waris: asas pribadi, asas bilateral, dan asas penderajatan. Disamping itu juga mengatur unsur-unsur hukum waris, seperti ahli waris, pewaris, dan harta waris sebagai harta yang diberikan pewaris kepada ahli warisnya. KUHPerdata juga membagi ahli waris menjadi empat golongan: Golongan I, Golongan II, Golongan III, dan Golongan IV.